A Chinese doctoral student's experience of L2 English academic writing in Australia: Negotiating practices and identities. Issue 49 (January 2021) - Wang, Meihui; Parr, Graham
Abstract: Increasing numbers of international students are choosing to study abroad at English speaking universities, where their L2 English academic writing is assessed alongside local students' L1 writing. Research has investigated the difficulties these student writers encounter, the deficits in their L2 academic writing products, and the strategies used to address these deficits. However, there has been little investigation into the experiences of L2 student writers of academic texts in particular international contexts, and the identity work associated with negotiating linguistic, cultural and institutional dimensions of these experiences. This narrative-based, qualitative case study addresses this gap in the literature by investigating the L2 English academic writing experiences of one Chinese student in an Australian university over the four years of her PhD candidature. Drawing on Bakhtinian dialogic theories of language and identity, in association with Gee's theorising of identity, the authors show how the challenges experienced by the Chinese student both constrained and facilitated her writing practices. An ongoing process of negotiating tensions in her writer identity mediated these practices, surfacing differing dimensions of the student's bilingual, transcultural, researcher-writer identity. The study offers recommendations for how students, academic supervisors and institutions can support this nuanced process of negotiation. Highlights: L2 English academic writing was challenging for a postgraduate Chinese student in Australia. The challenges constrained and facilitated her writing and her identity development. The Chinese student negotiated dialogic practices to address these challenges. Her university offered a generative third space that mostly supported this negotiation. Narrative-based case study showed nuanced socio-cultural insights into the experience.